A fatal case of multi-organ failure in acute yellow phosphorus poisoning - Jai Prakash Soni; Pankaj Suresh Ghormade; Swapnil Akhade; Krishnadutt Chavali; Bedanta Sarma (University of São Paulo, 2020)
Phosphorus is a nonmetallic irritant used in various sectors like rodenticide, firecracker industries, match industries, and fertilizers. Phosphorus poisoning is responsible for deaths among children and adults. Accidental yellow phosphorus poisoning is frequently reported in children, whereas suicidal consumption is not uncommon amongst adults. Herein, we present the case of a 30-year-old female patient who ingested Ratol paste containing yellow phosphorus in an attempt to commit suicide. Her initial chief complaints were nausea, vomiting along with loose motion during hospitalization, followed by a symptomless phase with stable vitals on the 2nd day, and managed conservatively. She took discharge against the medical advice. Later on, she was readmitted in the same hospital, after two days, complaining of generalized weakness, bodily pain, drowsiness, loss of appetite, and breathing difficulties. She developed severe complications due to the intoxication and died. An autopsy was performed. The histopathological and the toxicological examination were carried out. We found characteristic features in different organs due to yellow phosphorus toxicity. We concluded the cause of death as hepatic encephalopathy and multi-organ dysfunction syndrome caused by the yellow phosphorus poisoning.